Skill Membatik Dalam Meningkatkan Kesejahteraan Psikologis Pada ODGJ - Fahira Irba Yaumi; Ati Kusmawati (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2024)
People with mental disorders (ODGJ) need special attention and support so they can live more independently and prosperously. Individual empowerment is an effective approach to provide support and assistance for ODGJ in improving their psychological well-being and improving the individual's quality of life. This research will explore how ODGJ are able to channel their potential through involvement in batik skills. This research uses a qualitative approach which aims to obtain an overview of individual empowerment through batik skills in improving the psychological well-being of ODGJ at the Bina Laras Harapan Sentosa Social Home 3. Based on the research results, empowering batik skills at PSBLHS3 has a positive impact on the psychological well-being of ODGJ by exploring potential , increase creativity, and form positive attitudes and improve the quality of social relationships. The program provides opportunities for autonomy, self-acceptance, and positive social interactions, thereby improving mental health and overall well-being. Thus, empowering batik skills has helped improve the psychological well-being of ODGJ at the Bina Laras Harapan Sentosa 3 Social Home. Batik skills are an effective means of providing support, empowerment and improving the quality of life for social assistance residents with mental disorders.